Pemanfaatan Aplikasi Telegram dan Internet of Things Pada Pemantauan Tempat Sampah - Andhika Alif Arsadi; Emy Haryatmi (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2021)
Government implemented Standard Operating Procedure (SOP) for sanitation as main program. Trash can one of the storage which is regularly accessed by people to throw the garbage in housing area or public place such as shopping centre, train station and others. People are encouraged not to touch the trash can when they want to throw the garbage. People are supposed to wash their hand as soon as they touch the trash can. The objective of this research is to maintain the height of garbage in the trash can dan control the lid of trash can using telegram application. Bot telegram connected to microcontroller, motor servo and ultrasonic sensor was able to maintain the height of garbage and control the lid of trash can. People can use this system to throw the garbage in the trash can. Janitor also can use this system to empty the trash can before it full.